Solvothermal synthesis and characterization of Iron oxide nanoparticles - Jeyanthinath Mayandi, (Malaysian NANO-An International Journal, 2022)
In the present study, we investigated the crystallinity, surface morphology, and optical properties of iron oxide (Fe3O4) nanoparticles (NPs) formed by solvothermal synthesis. From powder XRD analysis, the Fe3O4 NPs were found to be an inverse spinel structure and highly crystalline nature. The surface morphology and particle size distribution were analyzed using a scanning electron microscope (SEM). The elemental compositions were confirmed using energy-dispersive X-ray spectroscopy (EDX). The optical characteristics of the Fe3O4 NPs were analyzed by UV-Vis spectroscopy. Overall, from the analysis, Fe3O4 NPs with tailored optical and structural properties can be easily formed by the solvothermal route to find potential applications in industries and the medical field.